Microwave assisted acid hydrolysis for bioethanol fuel production from sago pith waste - Saravana Kannan, Thangavelu; Rajkumar, T.,; Dinesh Kumar, Pandi; Abu Saleh, Ahmed; Farid Nasir, Ani (Elsevier Ltd, 2019)
Microwave assisted acid hydrolysis (H 2 SO 4 and HCl with >0.5 mol/L) to produce bioethanol from sago pith waste (SPW) was studied. The energy consumption for microwave hydrolysis at different energy inputs and acid concentration were calculated. The overall energy consumption for bioethanol fuel production from SPW was assessed. A maximum of 88% glucose yield and 80% ethanol yield (3.1 g ethanol per 10 g SPW) were obtained using 1.0 mol/L H 2 SO 4 . Microwave hydrolysis using 1.0 mol/L H 2 SO 4 consumed the minimum energy of 8.1 kJ to produce 1 g glucose from SPW when energy input was fixed at 54 kJ (900 W for 1 min). In general, 1 g glucose can produce 16 kJ. The overall energy consumption for fuel grade bioethanol production from SPW was 31.77 kJ per g ethanol, which was slightly higher than the lower heating values of ethanol (26.74 kJ/g ethanol). © 2019 Elsevier Ltd